2020
DOI: 10.3390/ijerph17134655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Physical Exercise Program in the Anxiety and Depression in Children with Obesity

Abstract: (1) Background: The high prevalence of childhood obesity and its multicausal etiology make it necessary to approach it through different strategies, whose objective is to promote the physical, mental, and social well-being of children. Regular physical activity, in addition to having positive effects on the physical environment of those who practice it, influences positively in psychological aspects such as anxiety and depression, which are very frequent in children with obesity and overweight. (2) Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…40 In 1 study, participants were recruited in a school, but activities were delivered outside school hours. 41 Two studies were conducted in summer camps 39 , 46 ; the setting was unclear in 1 of the studies 24 ( Table 2 ). 20–50…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…40 In 1 study, participants were recruited in a school, but activities were delivered outside school hours. 41 Two studies were conducted in summer camps 39 , 46 ; the setting was unclear in 1 of the studies 24 ( Table 2 ). 20–50…”
Section: Resultsmentioning
confidence: 99%
“…Significant reductions in anthropometric outcomes were reported in 10 of the 29 studies, 21–23 , 25 , 33 , 36 , 38 , 47–49 9 reported no significant changes, 20 , 26 , 27 , 34 , 35 , 40 , 41 , 43 , 44 and the effect of the intervention was unclear in 5 studies. 24 , 32 , 37 , 39 , 45 In 2 studies, 28 , 50 significant changes were reported in some, but not all, of the anthropometric outcomes considered (eg, changes in skin folds, but not in BMI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity (PA) helps to prevent childhood obesity and has significant psychological benefits on children with obesity, including improvement in emotional well-being, self-perception, and self-confidence ( Estabrooks et al, 2008 ; Katzmarzyk et al, 2015 ; Romero-Pérez et al, 2020 ). United States PA guidelines recommend 60+ min of age-appropriate, enjoyable, mostly moderate, or vigorous daily PA (MVPA) for children ( U.S. Department of Health and Human Services, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%